Pengaruh Program Keluarga Harapan Untuk Kesejahteraan Masyarakat Menurut Perspektif Ekonomi Islam - Pramujianto; Shomadani, M. Haikalus; Masyhuri (Jurnal Istiqro, 2024)
This research aims to find out the program keluarga harapan for the welfare of society in an Islamic economic review, using qualitative research methods and a descriptive approach. The results of this study are that the PKH assistance program has an impact on the welfare of the Karangjati village community, with PKH assistance the community can be assisted in meeting their needs and requirements in education and health, in terms of Islamic economics PKH assistance provides social security through complementarity provided in accordance with the rules that have been made by the Indonesian Ministry of Social Affairs, that the social security provided is health insurance and education insurance, so that PKH beneficiaries directly get this social security.